﻿A world checklist of extant and extinct species of Megaloptera (Insecta: Neuropterida) - Martins, Caleb C.; Ardila-Camacho, Adrian; Rivera-Gasperín, Sara Lariza; Oswald, John D.; Liu, Xingyue; Contreras-Ramos, Atilano (European Journal of Taxonomy, 2022)
A global synonymical checklist of the species and higher taxa of the insect order Megaloptera is provided. The checklist includes both extant and extinct taxa, and recognizes 2 families, 4 subfamilies, 48 genera, 425 species, and 6 subspecies. Both families (Corydalidae and Sialidae), and three of the four subfamilies (Corydalinae, Chauliodinae, and Sialinae) are known from both extant and extinct species; the Sharasialinae (Sialidae) is entirely extinct. Country-level geographic distribution data are provided for all species and subspecies. Synoptic type data are provided for taxa in the family and genus groups. Summary data are given for the numbers of megalopteran species currently known to occur in each of the major biogeographical regions of the world, and for the world fauna. Increase of knowledge about the diversity of the world Megaloptera fauna is summarized in counts of valid species described per decade and in a global taxonomic description curve. An updated set of keys to the world families, subfamilies, and genera of the Megaloptera is also provided.